Enhancing CaO2 fenton-like process by Fe(II)-oxalic acid complexation for organic wastewater treatment. (15th October 2019) - Yuan, Deling; Zhang, Chen; Tang, Shoufeng; Li, Xue; Tang, Jiachen; Rao, Yandi; Wang, Zhibin; Zhang, Qingrui
Abstract: Hydrogen peroxide (H2 O2 ) is used widely as Fenton's reagent for organic wastewater treatment. However, the application range of the optimum Fenton reaction is narrow, needing to adjust pH before and after treatment. Besides, the disproportionation of H2 O2 and generated iron precipitation also confine the normal operation of Fenton method. To overcome the drawbacks of the traditional Fenton process, a Fe(II) catalyzed calcium peroxide (CaO2 ) Fenton-like process assisted by oxalic acid (OA) for aqueous organic pollutants degradation was proposed (Fe 2+ /OA/CaO2 ). The methyl orange (MO) as a typical organic pollutant, its removal performances by this Fe 2+ /OA/CaO2 system were evaluated. In the optimized conditions, 99% of MO was degraded within 15 min, and 38% mineralized after 180 min when the molar ratio of Fe 2+ : OA: CaO2 was 1: 2: 2 (Fe 2+  = 1.5 mM). Radicals detection indicated that hydroxyl radical (HO ) was the main reactive species for the MO elimination. Furthermore, density functional theory calculation was in good agreement with the experimental results, which proved that the Fe 2+ /OA/CaO2 could improve the circulation between Fe 2+ and Fe 3+, promoting the oxygen reactive species generation and pollutant removal. The main intermediates were identified and the degradation pathways were proposed based on the results of the mass spectrum analysis, and the attack of HO was suggested as the main function for the MO decomposition. The matrix effects of water constituents on the performance of Fe 2+ /OA/CaO2 were investigated, and the results showed that a certain amount of Cl −, NO3 −, HCO3 −, and HA affected the elimination than SO4 2− . Finally, the attempt of actual wastewater disposal indicated the synergistic system possessed good potential for future practical application. Graphical abstract: Image 1 Highlights: The addition of OA significantly improved the CaO2 Fenton-like system. HO., O2 − ∙, and 1 O2 were identified as the main active substances in the Fe 2+ /OA/CaO2 . DFT calculation simulated and proposed the reaction mechanism of complexation system.